2012
DOI: 10.1002/nau.22321
|View full text |Cite
|
Sign up to set email alerts
|

Is there correlation between electromyography and digital palpation as means of measuring pelvic floor muscle contractility in nulliparous, pregnant, and postpartum women?

Abstract: There was a correlation between pelvic floor muscle contractility measured by surface electromyography and by digital palpation. Both methods can be used to validate data in research and clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 21 publications
1
51
0
5
Order By: Relevance
“…Currently, there is no evaluation tool that is considered the gold standard, which makes the comparison of results difficult and imprecise13. The International Continence Society recommends that functional evaluation of the pelvic floor should be performed through visual inspection, digital palpation, perineometry or electromyography14.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is no evaluation tool that is considered the gold standard, which makes the comparison of results difficult and imprecise13. The International Continence Society recommends that functional evaluation of the pelvic floor should be performed through visual inspection, digital palpation, perineometry or electromyography14.…”
Section: Introductionmentioning
confidence: 99%
“…However, other authors (20) reported a strong correlation between EMG and TDP in continent women without PFM disorders, showing that the best methods of PFM assessment are somehow controversial. In our study, we assessed PFM strength through transvaginal digital palpation in anterior and posterior areas and observed statistical concordance between both methods in 76% of cases, demonstrating that this assessment may be used in any of these positions.…”
Section: Discussionmentioning
confidence: 94%
“…SEMG analyzes muscle function from its electrical activity [18] and 3DUS provides information on muscle position, thickness and size, i.e. anatomical information [19].…”
Section: Discussionmentioning
confidence: 99%